An advanced prediction model for postoperative complications and early implant failure. Issue 10 (31st July 2020) - Feher, Balazs; Lettner, Stefan; Heinze, Georg; Karg, Florian; Ulm, Christian; Gruber, Reinhard; Kuchler, Ulrike
Abstract: Objectives: Risk prediction in implant dentistry presents specific challenges including the dependence of observations from patients with multiple implants and rare outcome events. The aim of this study was to use advanced statistical methods based on penalized regression to assess risk factors in implant dentistry. Material and methods: We conducted a retrospective study from January 2016 to November 2018 recording postoperative complications including bleeding, hematoma, local infection, and nerve damage, as well as early implant failure. We further assessed patient‐ and implant‐related risk factors including smoking and diabetes, as well as treatment parameters including types of gaps and surgical procedures. Univariable and multivariable generalized estimating equation (GEE) models were estimated to assess predictor effects, and a prediction model was fitted using L1 penalized estimation (lasso). Results: In a total of 1, 132 patients (mean age: 50.6 ± 16.5 years, 55.4% female) and 2, 413 implants, postoperative complications occurred in 71 patients. Sixteen implants were lost prior to loading. Multivariable GEE models showed a higher risk of any complication for diabetes mellitus ( p  = .006) and bone augmentation ( p  = .039). The models further revealed a higher risk of local infection for bone augmentation ( p  = .003), and a higher risk of hematoma formation for diabetes mellitus ( p  = .007) and edentulous jaws ( p  = .024). The lasso model did not select any risk factors into the prediction model. Conclusions: Using novel methodology well‐suited to tackle the specific challenges of risk prediction in implant dentistry, we were able to reliably estimate associations of risk factors with outcomes.